Sabotage at Cedar Creek [large type] - Thompson, Janice A. (Thompson, Janice A. Little red truck mysteries, 2025)
"In Mabank, Texas, the Hadley family's new antique business is open and running well with Tilly, the red antique truck, as its mascot. RaeLyn Hadley enjoys driving Grandpa's truck around as she seeks out antiques for her family's store. RaeLyn is excited that her friend, Tasha, will soon open a new vacation rental home to accommodate the area's growing tourism, but an act of vandalism threatens to spoil all Tasha has worked for. RaeLyn immediately gets to work sleuthing out who could be behind such an act of sabotage. Could it be the nearby resort owner; the daughter of the house's former owner; a neighbor; or a squatter who had been living in the house before renovations? RaeLyn is determined to solve the mystery for her friend."--